Pengaruh Motivasi, Kesehatan Kerja, dan Keselamatan Kerja (K3) Terhadap Kinerja Karyawan PT. X di Bumi Serpong Damai - Riptono Riptono; Muhammad As’ad; Mochamad Reza Hafriansyah (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
This research aim to analyze the effect of Motivation, Occupational Health, and Safety (OHS) on Employee Performance.The amount of population are 70 employee in PT X  and 59 people were sampled by Morgan & Krecjie table.Based on research resultsindicates that: Partially show that motivation has a positive and significant influence amounted to 78,9% of employee Performance. In the second Partial results showed that Occupational Health has no positive and significant impact on employee performance by 19%. In the third Partial results showed that Safety has an inverse and significant impact by 60,1% on Employee Performance. The independent variables Motivation, Occupational Health, and Safety are jointly tested by F test proved positive and significant influence on Employee Performance and the magnitude of the effect seen from coefficient of Determination (R2) is 35,4%.